The issue of alcohol abuse among the youth – students of Lublin schools - Książek, Piotr; Dreher, Piotr; Dreher, Sylwia; Jurek, Anna; Budzyńska, Agnieszka; Husarz, Renata (Polish Journal of Public Health, 2016)
Introduction. Alcohol abuse among the youth is a pressing social issue. It is not only related to one’s individual susceptibility to risky or harmful drinking but also the issue of one’s family living with the individual that abuses alcohol. It needs emphasizing that alcohol consumption is on the rise and the age at which young people have their first alcoholic drink is declining as well. Also, girls tend to drink as much as boys. Aim. The aim of this work was to investigate the issue of alcohol abuse among young people of school age and the relationship between the following variables: school educational level, sex, satisfaction with home life and drinking patterns. Material and methods. The authors interviewed some 1 444 students of 32 schools (12 elementary schools, 10 junior high schools and 10 high schools) chosen at random, using an anonymous questionnaire. The collected data were analyzed statistically, taking the following factors into consideration: sex, school level, atmosphere at home. Results and conclusions. One’s sex, school level and satisfaction with home life had influence over the respondents’ answers concerning alcohol consumption. The research study shows that students of schools at all levels drink alcohol – high school students drink vodka, junior high school students (gimnazjum in Polish) prefer beer, while elementary school students, who tend to drink the least, prefer wine. Interestingly enough, boys are drinking more than girls, yet girls are more likely to try all types of alcohol. Children who reported good atmosphere at home are less likely to drink, while in case of troubled homes, only every eighth respondent does not drink. The atmosphere at home also affects one’s drinking habits. Most of the respondents have no idea about ways of helping people addicted to alcohol.